Wanprestasi Dalam Perjanjian Makan Hasil Dusun - Irawati Rommer; Teng Berlianty; Sarah Selfina Kuahaty (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
There is a shape of agreement to enjoy the results of the community in Kehly Village, Damer Island District, Southwest Maluku Regency, which is commonly known as